Принципы построения мультиагентной платформы для имитационного моделирования процессов в бизнесе - Валькман, Ю.Р.; Муцаковска, Е.В. (Моделювання та інформаційні технології, 2011)
This research covers developing the concept of building software for agentbased simulation of business processes in BPMN notation. Building such a system would enable in-depth analysis and visualization of real business.